2006
DOI: 10.1007/s00122-006-0437-5
|View full text |Cite
|
Sign up to set email alerts
|

A microsatellite marker based linkage map of tobacco

Abstract: We report the first linkage map of tobacco (Nicotiana tabacum L.) generated through microsatellite markers. The microsatellite markers were predominantly derived from genomic sequences of the Tobacco Genome Initiative (TGI) through bioinformatics screening for microsatellite motives. A total of 684 primer pairs were screened for functionality in a panel of 16 tobacco lines. Of those, 637 primer pairs were functional. Potential parents for mapping populations were evaluated for their polymorphism level through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
115
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 25 publications
4
115
0
5
Order By: Relevance
“…The D′ values ranged from 0.01 to 0.82 with the average value of 0.268. Using MLM procedure based on Q + K model 1 SSR locus (pt30027) from linkage group 13 (Bindler et al 2007) was identified that possessed significant association (P ≤ 0.04) with the QTL controlling chloride accumulation rates in oriental-type tobacco genotypes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The D′ values ranged from 0.01 to 0.82 with the average value of 0.268. Using MLM procedure based on Q + K model 1 SSR locus (pt30027) from linkage group 13 (Bindler et al 2007) was identified that possessed significant association (P ≤ 0.04) with the QTL controlling chloride accumulation rates in oriental-type tobacco genotypes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six SSR primer pairs out of 278 from the tobacco SSR database (Bindler et al 2007(Bindler et al , 2011 were used for DNA fingerprinting. The choice of SSR markers was based on their known genetic locations to obtain near-uniform coverage of the tobacco genome and clarity of produced bands (Bindler et al 2007(Bindler et al , 2011. PCR was performed in a 20 µl volume using a 96-well Eppendorf Mastercycler Gradient (Type 5331, Eppendorf AG, Hamburg, Germany).…”
Section: Genotypic Datamentioning
confidence: 99%
“…However, this does not include a protocol for the novel marker selection/identification, but rather exploits the markers generated for a closely related species N.tabacum (Bindler et al, 2007). This is a high-throughput protocol optimized and streamlined for one skilled person to process 384 (96 x 4) seeds in 5 days, from DNA isolation (from seedlings) to paternity assessment by microsatellite genotype data.…”
mentioning
confidence: 99%
“…tabacum (Bindler et al, 2007). This is a high-throughput protocol optimized and streamlined for one skilled person to process 384 (96 x 4) seeds in 5 days, from DNA isolation (from seedlings) to paternity assessment by microsatellite genotype data.…”
mentioning
confidence: 99%
“…Nicotiana pertence à família das solanáceas e subdivide-se em três subgenêros: Rustica, Tabaccum e Petunioides (GOODSPEED, 1954 apud REN;TIMKO, 2001). O gênero Nicotiana, além da relevância econômica, é considerado um importante modelo para estudo na área de biotecnologia e, ainda, como auxiliar em estudos que envolvem princípios de resistência a doenças, síntese de metabólitos secundários e fisiologia de plantas (BINDLER et al, 2007).…”
Section: Nicotiana Tabacum L é Uma Espécie Tetraplóide Resultante Daunclassified